Potential dsRNAs can be delivered to aquatic for defense pathogens - Nie, Wenhao; Chen, Xiaojiao; Tang, Yueyao; Xu, Nianjun; Zhang, Hao (Frontiers in Bioengineering and Biotechnology, 2022)
The use of antibiotics to facilitate resistance to pathogens in aquatic animals is a traditional method of pathogen control that is harmful to the environment and human health. RNAi is an emerging technology in which homologous small RNA molecules target specific genes for degradation, and it has already shown success in laboratory experiments. However, further research is needed before it can be applied in aquafarms. The current laboratory method used for dsRNA administration is mainly through injection, which is obviously impractical and very time consuming in aquafarms. Therefore, to enable the use of RNAi on a large scale, the methods used to prepare dsRNA need to be continuously improved to reduce costs. Moreover, at the same time, it is necessary to consider the issue of biological safety. This review summarizes the key harmful genes associated with aquatic pathogens (viruses, bacteria, and parasites) and provides potential targets for the preparation of dsRNA; it also lists some current examples where RNAi technology is used to control aquatic species, as well as promising ways to prepare dsRNA.